Untitled: pottery and drawing - Veerkamp, Patrick B., author; Hendry, Kenneth, advisor; Dietemann, David L., committee member; Williams, Ron G., committee member; Twarogowski, Leroy A., committee member (Colorado State University. Libraries, 1981)
My work originates from the personal experience and perception of the dichotomous nature of reality. My concern is with the interface of this twofold state. Metaphorically, I am exploring a hypothetical line of demarcation - the median - the verge of; classical and romantic, order and disorder, etc., the brink of transition from one position to the other. My intent is not merely to make known a duality but to explore mutual interactions and complexities within this relationship; the irony of the subtle conflicts and harmonies that result from this confrontation. TACIT RECONCILIATION - Each piece involves the juxtaposition of disparate plastic elements. The individual components are allowed to interact in contrast or in harmony, coexisting in a common space. In order to facilitate this union of contrasting parts certain mediating devices are employed to reconcile the inherent duality. Pottery, and its innate abstract associations, is one such device; the dynamic symmetry of specific proportional relations is another. The result is an intermingling of dissimilar elements within the structure of 'known' organizational principles. In effect the security of this known structure is countered by the insecurity and ambiguity of contrasting plastic means. Thus, the image becomes an intermediary, a compromising factor between unyielding extremes. It is an agent for a complex experience capable of accommodating such diverse feelings as anxiety, serenity, frustration, fulfillment and a similar variety of conflicting emotions. Ultimately, it serves to mediate a new state of experience interposed between antipodal positions. This experience is tacit, i.e., it cannot be perceived by stating directly the dichotomous premises but it is inferred by the reconciliation of the two. In fact, it must evade the extremes in order to mediate the intervening position - it is my thesis that this is the most complete and richest experience.
Keywords: Terra-cotta; Drawing